2006
DOI: 10.1016/j.neuropsychologia.2005.07.013
|View full text |Cite
|
Sign up to set email alerts
|

l-dopa impairs learning, but spares generalization, in Parkinson's disease

Abstract: In this study we examined the effect of dopaminergic modulation on learning and memory.Parkinson's patients were tested 'on' versus 'off' dopaminergic medication, using a two-phase learning and transfer task. We found that dopaminergic medication was associated with impaired learning of an incrementally acquired concurrent discrimination task, while patients withdrawn from dopaminergic medication performed as well as controls. In addition, we found a dissociation of the effect of medication within a single two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
148
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 139 publications
(170 citation statements)
references
References 53 publications
(87 reference statements)
21
148
1
Order By: Relevance
“…Untransformed values are presented in tables and figures. In addition, following Shohamy et al (2006) and Myers et al (2002), we also analyzed whether the subject passed criterion or not on the learn and relearn phases: this was done with a Fisher's exact test on each phase separately.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Untransformed values are presented in tables and figures. In addition, following Shohamy et al (2006) and Myers et al (2002), we also analyzed whether the subject passed criterion or not on the learn and relearn phases: this was done with a Fisher's exact test on each phase separately.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease, PD) were shown previously to be dependent on dopamine medication: medicated but not unmedicated PD patients were impaired on the task Shohamy et al, 2006). It has been suggested that dopaminergic medication may 'overdose' cognitive functions dependent upon ventral striatal-orbitofrontal circuitry (Cools et al, 2001;Cools, Barker, Sahakian, & Robbins, 2003 2000), which are relatively intact in the early stages of PD (Kish, Shannak, & Hornykiewicz, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, there is a more pronounced reduction of dopamine in the dorsal than in the ventral striatum (Kish et al, 1988). Therefore, therapies that restore dopamine level in the dorsal striatum result in dopamine 'overdose' in the ventral striatum, which may lead to impaired performance on some cognitive tasks (Gotham et al, 1988;Cools et al, 2001Cools et al, , 2003Shohamy et al, 2006;Jahanshahi et al, 2010;MacDonald et al, 2011) and in some cases psychotic symptoms, including hallucinations and delusions (McGowan et al, 2004;Mehler-Wex et al, 2006;Maia and Frank, 2011). At the same time, there is evidence that dopaminergic therapy enhances learning from reward signals and decreases learning from punishment signals in PD (Frank et al, 2004(Frank et al, , 2007Cools et al, 2006;Bódi et al, 2009;Graef et al, 2010;Kobayakawa et al, 2010), and the ventral striatum has a crucial role in reinforcement learning (Yin and Knowlton, 2006).…”
Section: Introductionmentioning
confidence: 99%